Use of Oral Corticosteroids and Risk of Hip Fracture in the Elderly in a Case-Control Study - Lai, Shih-Wei (Front Pharmacol, 2017)
Aim: Little is known regarding the relationship between use of oral corticosteroids and hip fracture in the elderly in Taiwan. The aim of the study was to examine this issue. Methods: A retrospective population-based case-control study using the database of the Taiwan National Health Insurance Program (2000–2013) was conducted. We identified 4538 individuals aged ≥ 65 years with newly diagnosed hip fracture as the cases. We randomly selected 4538 individuals without hip fracture as the control subjects. The cases and the control subjects were matched with sex, age, comorbidities, and the year of index date. Individuals who never had a prescription for oral corticosteroids were defined as never use. Individuals who ever had at least one prescription for oral corticosteroids were defined as ever use. The odds ratio (OR) and 95% confidence interval (CI) of hip fracture associated with oral corticosteroids use was estimated by a multivariable unconditional logistic regression analysis. Results: After adjustments for potential confounding factors, the multivariable logistic regression model showed that the adjusted OR of hip fracture was 1.17 for individuals with ever use of oral corticosteroids (95%CI 1.08, 1.28), compared to those with never use of oral corticosteroids. An sub-analysis showed that for every 1-mg increase in cumulative dose of oral corticosteroids, the adjusted OR of hip fracture was 1.01 (95% CI 1.01, 1.02). The adjusted ORs were 1.31 (95% CI 1.17, 1.47) for cumulative exposure to oral corticosteroids ≥ 3 months and 1.09 (95% CI 0.98, 1.20) for cumulative exposure < 3 months. Conclusion: We conclude that oral corticosteroids use is associated with a trivial but statistically significant increase in risk of hip fracture in Taiwan. Additionally, the results suggest that there are dose-response and duration-response effects of oral corticosteroids on the risk of hip fracture. The results confirm our understanding of oral corticosteroid-associated hip fracture in the elderly.